Desain Pembelajaran Matematika Berbasis Etnomatematika untuk Menjadikan Laboratorium Matematika yang Inovatif Di IAIN Curup - Syaripah Syaripah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The purpose of research in mathematics learning is to obtain the needs of lecturers and students of Tadris Mathematics IAIN Curup, to plan the development, design, design, design, effectiveness of ethnomathematics-based learning to make an innovative mathematics laboratory. This type of research is a mixed method that is a combination of quantitative and qualitative research. The Plomp model phase consists of an investigation phase, a design phase, a realization/construction phase, a test phase, an evaluation, and a revision and implementation phase. This research was carried out on Tadris Mathematics students of IAIN Semester IV Academic Year 2018/2019 The results of the perception questionnaire of Tadris Mathematics lecturers and students showed 72% of students and 100% of lecturers stated that the mathematics learning used so far was not appropriate. Initial design planning for the development of ethnomathematical-based Geometry Transformation teaching materials.Study book design with 5 (five) chapters consisting of 42 pages and a bibliography. The results of RPS/SAP validation with an average of 3.24 categories are quite good with slight revisions, 3.15 textbook categories are good enough so that they can be used with slight revisions and LKM with an average of 3.03 categories are quite good with revisions. The results of the practicality of the book obtained an average of 4.38 in the good/practical category, the practicality of the LKM with an average of 4.45 in the good/practical category and the practicality response of learning mathematics with an average of 91.7% which means it is very practical. The results of the effectiveness of learning mathematics obtained from observations of lecturer activities assessed by observers, obtained 84% of lecturer activities according to RPS.